Editorial - Soares, Adriana Benevides; Feijoo, Ana Maria; Uziel, Anna Paula; Ewald, Ariane Patrícia; Mancebo, Deise; Prestrelo, Eleonôra Torres (Estudos e Pesquisas em Psicologia, 2008)
Adriana Benevides Soares, Ana Maria Feijoo, Anna Paula Uziel, Ariane Patrícia Ewald, Deise Mancebo, Eleonôra Torres Prestrelo